"Self-centered, self-promoting, and self-legitimizing": CNN's portrayal of media ownership concentration in the US. Issue 5 (20th October 2021) - Herzog, Christian; Scerbinina, Alise
ABSTRACT: In late 2017 the potential merger between AT&T and Time Warner was blocked while two other comparable media deals were not penalized. Drawing on a critical political economy of communications framework, this article investigates CNN online news' portrayal of media-ownership concentration in the US. We subjected the news coverage (n = 43) of CNN (a subsidiary of Time Warner) to a thematic analysis along the lines that Braun and Clarke suggest. The results show that CNN's coverage of media ownership concentration developments can be described as self-centered, self-promoting, and self-legitimizing. While the main focus is on news coverage the article offers an account of the different handling of the three mergers by the Trump administration, the Department of Justice and the Federal Communications Commission. The mergers show high levels of politicized intervention. We seek to contextualize and partly explain these findings with contradictions in the present conjuncture.